Pengaruh Ambiguitas Perandan Work Family Conflict Terhadapstres Kerja Pegawai PT. Asuransi Mega Pratama Cabang Padang - Yoki Febri Kasmi; Rini Sarianti; Hendri Andi Mesta (Jurnal Praktik Bisnis, 2019)
This study aims to obtain empirical evidence of the influence of role ambiguity, and work family conflict against employee work stress PT. Insurance Mega Pratama Padang Branch. In this study used as many as 52 employees of PT. Insurance Mega Pratama Padang Branch. Sampling was done using census method. The research variables used include independent variables that are role ambiguity and work family conflict while the dependent variable is job stress. The results of hypothesis testing showed that: 1) the ambiguity of the role have a positive and significant effect on employee work stress PT. Insurance Mega Pratama Padang Branch. 2) work family conflict does not have a significant effect on employee work stress PT. Insurance Mega Pratama Padang Branch.